Neuroengineering the future virtual minds and the creation of immortality - Katz, Bruce F. (Infinity Science Press, 2008)
Describing how the brain works, this book includes an overview of the architecture of the brain. It examines the neural technologies, including devices that read from the brain, and devices that can write information into the brain.